A CASE FOR NATIONAL INCOME ACCOUNTING IN THE ACCOUNTING CURRICULUM. - Smyth, J. E. (The Accounting Review, 1959)
Abstract The subject of this paper is closely related to one's philosophy of education. Those who favor a curriculum which provides for breadth of outlook will differ in the means by which their objective may best be achieved, but some attention to national income accounting is merited. To provide its students with as wide a knowledge and understanding of the world they live in as is possible by the time they finish their formal education is an aim worthy of a school of business–in common with the university of which it forms a part.